Measuring the Sustainability Performance of EU Countries through a Composite Multidimensional Index - Mikča, Radoslav; Huttmanová, Emília (European Journal of Sustainable Development, 2025)
This paper proposes a sustainability index that captures the economic, environmental, and social performance of EU countries. Using a set of standardized indicators grouped into three dimensions, we construct sub-indices for each pillar and aggregate them into a composite score. The index reflects the multidimensional nature of sustainability and enables cross-country comparison. The main objective of this paper is to construct a composite sustainability index for EU countries and analyze their multidimensional performance using PCA and cluster analysis. Data is drawn from Eurostat and other relevant sources, covering recent years. To ensure comparability and robustness, we apply normalization techniques and explore weighting schemes through principal component analysis. The final index is analyzed spatially and statistically, identifying sustainability leaders and laggards within the EU. This approach contributes to the understanding of national sustainability dynamics and supports data-driven policy recommendations aimed at enhancing balanced progress across key domains. Key words: sustainability, sustainable development, SDG indicators, composite index, country clustering.